Case Study 3 - Gujarat, India : Participatory Approaches in Budgeting and Public Expenditure Management - World Bank (Washington, DC, 2012)
The state of Gujarat hosts almost a tenth of India's 80 million tribal people. Despite official rhetoric of significant investment in tribal development projects, results on the ground were questionable. This prompted DISHA (Development Initiatives for Social and Human Action) to get into the business of budget analysis in 1992 to ascertain what actually was happening to funds allotted in the name of the tribals under the Tribal Area Sub-plan. DISHA thus began by first taking up the issue of the state's 7.3 million forest laborers, not recognized as a formal professional group, but have since broadened the scope of their work to cover most aspects of budget analysis of general topics. Described as an attempt at "democratizing the budget process"2, DISHA obtains budget documents, reviews and disaggregates departmental allocations for different beneficiaries, researches the discrepancy between proposed and actual spending, and prepares briefs on synthesized findings for informed public debates. DISHA is one of the five largest membership-based NGOs in India with most of its 80,000 members drawn from tribal and forest workers. Although linked with its general analytical work on budgets, DISHA runs a separate lobbying and advocacy movement in favor of its huge tribal constituency.